1997
DOI: 10.1053/jhep.1997.v25.pm0009021955
|View full text |Cite
|
Sign up to set email alerts
|

The in vivo effect of hepatotrophic factors augmenter of liver regeneration, hepatocyte growth factor, and insulin-like growth factor-II on liver natural killer cell functions

Abstract: Fine balanced sequential changes of the levels of circulating hepatotrophic factors are essential for normal liver regeneration. Our recent studies have indicated that liver-resident natural killer (NK) cells are important regulators of liver regeneration and have raised the possibility that hepatotrophic factors might mediate their activities through NK cells. In the present study, we assessed the effects of in vivo administration of three hepatotrophic factors (augmenter of liver regeneration [ALR], insulin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 27 publications
(56 reference statements)
1
29
0
Order By: Relevance
“…An insightful finding is the modification of IL-10/ IFN-␥ gene transcription in LDC during the early phase of liver regeneration, and the ability of these cells to induce a similar cytokine pattern when co-cultured with naïve T cells. Notably, a decrease in IFN-␥ has already been demonstrated in the liver tissue and is associated with inhibition of hepatic NK cell lytic activity, 10 -a "physiological" event in the process of hepatocyte proliferation after PH. Furthermore, the concomitant increase in expression of IL-10, a well-known anti-inflammatory cytokine, suggests that LDC may be actively involved in promoting a state of local immune suppression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An insightful finding is the modification of IL-10/ IFN-␥ gene transcription in LDC during the early phase of liver regeneration, and the ability of these cells to induce a similar cytokine pattern when co-cultured with naïve T cells. Notably, a decrease in IFN-␥ has already been demonstrated in the liver tissue and is associated with inhibition of hepatic NK cell lytic activity, 10 -a "physiological" event in the process of hepatocyte proliferation after PH. Furthermore, the concomitant increase in expression of IL-10, a well-known anti-inflammatory cytokine, suggests that LDC may be actively involved in promoting a state of local immune suppression.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Although various genetic and biological factors that play a role in this phenomenon have been extensively investigated, [4][5][6][7][8] the mechanisms responsible for the initiation, maintenance, and suspension of hepatocyte proliferation have not been fully elucidated. Two aspects of liver regeneration that appear to be important are (1) strong inhibition of the cytotoxic activity of liver-resident natural killer (NK) cells, which becomes evident within a few hours after partial hepatectomy (PH) and terminates at the end of the regenerative process 9,10 ; and (2) a significant increase in circulating estrogen level and expression of estrogen receptors in tissue, regardless of gender or species. Partial hepatectomy in male animals is followed by an almost complete disappearance of serum androgens and their related tissue receptors in a process known as "feminization" of the male regenerating liver.…”
mentioning
confidence: 99%
“…The mitogenic and antiatrophic activities of native and cloned ALR were demonstrated in partially hepatectomized rats [1] and in dogs with portacaval shunt [2][3][4]6,7]. ALR also inhibits the lytic activity of hepatic natural killer cells [8,9], which is critical for unabated liver regeneration [10]. Presence of hepatotrophic activity in weanling and regenerating [1][2][3]11] but not in the unmodified adult animal livers [1,3] suggested that ALR is not synthesized by the latter.…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that NK cell cytotoxic activities were inhibited in the population of mononuclear leukocytes (MNL) in the liver (liver-resident NK cells ), but not in the MNL from the spleen or peripleral blood. Results obtained in vitro displayed that ALR, IGF-II and HGF had no effect on NK cell function in cultured MNL from the liver, spleen or blood [69] . Results from Polimeno et alalso verified that ALR plays a pivotal role as growth factor and as immunoregulator by controlling the mitochondrial transcription factor A expression and lytic activity of liver-resident NK cells through IFN-γ levels [70] and regulates hepatocyte proliferation through enhancing cytochrome content and oxidative phosphorylation capacity of liver-derived mitochondia [71] .…”
Section: Stimulation Of Hepatocyte Regenerationmentioning
confidence: 92%
“…Liverderived NK cells are important regulators for liver regeneration [68] . Francavilla et al [69] connected the regulation activity of ALR in liver regeneration with the novel role of NK cells. Francavilla et al administrated three hepatotrophic factors (ALR, insulinlike growth factor II [IGF-II] and HGF) with the surely inducing sound hepatotrophic activities to assess the in vivo effects on NK cells in normal rats.…”
Section: Stimulation Of Hepatocyte Regenerationmentioning
confidence: 99%